Indiviual Workload Perceptions Of Employee Health Workers In Hospitals - Gülcan Çiftçioğlu; Gülistan Tunç; Aynur Güneş; Vasfiye Değer; Sema Çifçi (Association of Nurse Managers, 2018)
INTRODUCTION: The workload refers to the time and energy requiredto do the job on an individual basis, and to the efficiency of the organization. Workload is a very important variable for the employee in organizational maintenance. The aim of this research is to reveal the perception level of health workers working in the state hospital with regard to working environment. METHODS: As a data collection tool in the research; Perceptions of health workers with regard to working environments were measured by using the "Individual Workload Perception Scale" and Personal Information Form. This scale was developed by Cox in 2003. While all of the health personnel (421 persons) working in the state hospital where research can be granted constitute the universe of the research; The sample consisted of 220 volunteers who participated in the survey from all health workers working in this hospital. Data were collected from 195 health workers.The data of the study were collected between October and November 2016. The collected data of this study were analyzed using the SPSS program Student's t-test analysis was used in the independent groups to evaluate the relationship between number, percentile and mean-standard deviation, independent variables and scale sub-dimensions. RESULTS: The average score of the subgroups of the scale is 103.7 +- 22.07. Average management support from sub-dimensions of working environment evaluation was found 3,63+-0,66 (n: 195), collegiality mean was found 3,73+-0,71 (n: 195), the average unit support was found 2,77+-0,58 (n = 195), mean working environment perceptions was found 3,52+-0,84 (n: 195), and average intention to continue the current business was found 1,04+-0,30 (n: 195), respectively. DISCUSSION AND CONCLUSION: In line with these results, it was found that health workers received the most workload support from their colleagues. It was found that health workers have the lowest scores about the intentions to maintain the same business.